2019
DOI: 10.1371/journal.pone.0217737
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ankle joint position on angles and distances of the ankle mortise using intraoperative cone beam CT: A cadaveric study

Abstract: Background The precise anatomical reduction of the ankle mortise is crucial for the clinical outcome in unstable syndesmotic injuries. Intraoperative cone beam computed tomography (CT), in addition to two-dimensional fluoroscopy, provides detailed information about the reduction and implant placement. The aim of this study was to analyze the influence of the joint position on the fibula position in the incisural notch and to determine the inter- and intraindividual anatomical differences in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Mirroring can only approximate the reality because it assumes that left and right ankles are truly symmetrical. Studies showed that the intra-individual variability is significantly lower than the inter-individual variability [ 5 ]. The input data consists of left and right ankles to generalize towards intra-individual variability eventually caused by biomechanical attrition.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mirroring can only approximate the reality because it assumes that left and right ankles are truly symmetrical. Studies showed that the intra-individual variability is significantly lower than the inter-individual variability [ 5 ]. The input data consists of left and right ankles to generalize towards intra-individual variability eventually caused by biomechanical attrition.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Reduction refers to the re-alignment of the dislocated bones whereas fixation refers to the attachment of metal implants to fixate the bones. Anatomical reduction is essential and incorrect reduction (malreduction) may cause instability and chondral degeneration leading to premature osteoarthritis [ 5 ]. Intra-operative imaging allows monitoring of the reduction result and implant positioning during all phases of an intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The position of the foot, according to the studies by Levack and Vetter, has no relevant influence on the tibiofibular distance nor on the tibiofibular angle. Therefore, the intraoperative scan can be performed in any position of the ankle and foot [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The position of the foot, according to the studies by Levack and Vetter, has no relevant in uence on the tibio bular distance nor on the tibio bular angle. Therefore, the intraoperative scan can be performed in any position of the ankle and foot [21,22].…”
Section: Discussionmentioning
confidence: 99%